2015
DOI: 10.1523/jneurosci.3720-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Projections from Lateral Hypothalamus to Paraventricular Hypothalamic Nucleus Promote Feeding

Abstract: Lesions of the lateral hypothalamus (LH) cause hypophagia. However, activation of glutamatergic neurons in LH inhibits feeding. These results suggest a potential importance for other LH neurons in stimulating feeding. Our current study in mice showed that disruption of GABA release from adult LH GABAergic neurons reduced feeding. LH GABAergic neurons project extensively to the paraventricular hypothalamic nucleus (PVH), and optogenetic stimulation of GABAergic LH ¡ PVH fibers induced monosynaptic IPSCs in PVH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 33 publications
7
71
0
Order By: Relevance
“…3H ). Combined with our previous data on LH neurons (Wu et al, 2015), these data suggest that Pdx1-Cre targets a major subset of non-POMC, non-AgRP GABAergic neurons in the hypothalamus.…”
Section: Deletion Of Vgat By Pdx1-cre In the Hypothalamussupporting
confidence: 78%
See 4 more Smart Citations
“…3H ). Combined with our previous data on LH neurons (Wu et al, 2015), these data suggest that Pdx1-Cre targets a major subset of non-POMC, non-AgRP GABAergic neurons in the hypothalamus.…”
Section: Deletion Of Vgat By Pdx1-cre In the Hypothalamussupporting
confidence: 78%
“…7E), although the degree in difference was smaller than those observed in Pdx1-Cre:Vgat flox/flox mice. We previously reported that Sim1-Cre:␥2 flox/ flox mice exhibited reduced nocturnal feeding (Wu et al, 2015). Associated with this, these mice showed specific attenuation in O 2 consumption during the dark period (Fig.…”
Section: Disrupted Gabaergic Input To the Pvh Reduced Postweaning Gromentioning
confidence: 53%
See 3 more Smart Citations